Kajian Semiotika Charles Sanders Peirce pada Sampul Buku “Seri Kenali Emosi” Tentang Anak - Hestia Rachmat Nunciata Lubis; Yosef Yulius; Rheina Anastasia Putri (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
This research aims to analyze the meaning and representation of emotions depicted on the covers of the “Seri Kenali Emosi” (Know Your Emotion Series) books, published by Tentang Anak. Adopting Charles Sanders Peirce’s semiotic approach, the study systematically analyzes the visual and textual signs present. The study’s core data consists of four specific book covers from the series, all release on July 23, 2022, a date chosen to align with National Children’s Day. Data collection involved both direct observation of these physical book covers, yielding concrete primary data, and a comprehensive literature review, where of relevant scholarly sources like books, journals, theses, and relevant websites. The analyzes involved identifying and categorizing visual and textual elements on each cover into Peirce’s three sign categories: icons (signs physically resembling their object), index (signs with a direct causal or existential links), symbols (signs whose meaning is based on convention). By applying this detailed semiotic analysis, this study investigates how three specific sign types work together to communicate complex emotional messages. The findings are expected to provide a comprehensive understanding of the semiotic strategies used in children’s book cover design, especially in depicting and communicating various emotional nuances effectively to young audiences and their parents.